2001
DOI: 10.1055/s-2001-12218
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy (1H-MRS) of the Cerebrum in Two Young Infants with Zellweger Syndrome

Abstract: Cerebral metabolic abnormalities have been previously detected by 1H-MRS in infants with the Zellweger syndrome as young as 3 months. We hypothesized that metabolic abnormalities could also be found shortly after birth. Two fullterm infants with Zellweger syndrome were studied at 12 days and two months of age, respectively, using single voxel 1H-MRS. In the first case 1H-MRS was performed using PRESS with variable TE (31, 136, 272 ms); in the second, STEAM and PRESS sequences were used with different TE (STEAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…In normal brain tissue, lipids are present in cell membrane and myelin sheath. When these structures are injured, the lipids are consequently released to generate free lipid molecules, which can be captured by MRS spectra at the wave crests of 0.9 ppm and 1.3 ppm (Groenendaal et al, 2001). Since Pb is known to generate free radicals and cause oxidative stress in brain (Bennet et al, 2007; Bolin et al, 2006; Chetty et al, 2007), the observed increase in Lip/Cr among Pb-exposed workers may reflect the Pb-induced lipid peroxidation in brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In normal brain tissue, lipids are present in cell membrane and myelin sheath. When these structures are injured, the lipids are consequently released to generate free lipid molecules, which can be captured by MRS spectra at the wave crests of 0.9 ppm and 1.3 ppm (Groenendaal et al, 2001). Since Pb is known to generate free radicals and cause oxidative stress in brain (Bennet et al, 2007; Bolin et al, 2006; Chetty et al, 2007), the observed increase in Lip/Cr among Pb-exposed workers may reflect the Pb-induced lipid peroxidation in brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The 1.3 ppm peak is several times taller than the 0.9 ppm peak in the mobile lipids commonly seen in toxoplasmosis, lymphomas and high-grade gliomas. Approximately equal-sized peaks have been seen in Zellweger syndrome (11,12), an example of which will be shown below and progressive multifocal leukoencephalopathy (PML) (13)(14)(15)(16)(17)(18). In contrast, a single broad peak usually indicates contamination with skull lipids.…”
Section: Appearance Of Lipid Peaksmentioning
confidence: 99%
“…5 1 H-MR spectroscopy shows ongoing metabolite changes during infancy. 6,7 Following its biochemical definition patients were identified with peroxisome biogenesis disorder (PBD), biochemically similar to but clinically different from ZS, having more prolonged survival, sometimes even into adulthood, and variability in clinical outcome. 8 ZS related PBD include neonatal adrenoleukodystrophy (NALD) 9,10 and infantile Refsum disease (IRD).…”
mentioning
confidence: 99%